2001
DOI: 10.1590/s0100-204x2001000300021
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da utilização da levedura desidratada de álcool em dietas para tilápia-do-nilo

Abstract: Resumo Este trabalho teve como objetivo avaliar o efeito da levedura desidratada de álcool (Saccharomyces cerevisae) como substituto do suplemento vitamínico, em dietas de tilápia-do-nilo (Oreochromis niloticus). Trezentos alevinos machos, sexualmente revertidos, com peso médio de 1,5 g, foram distribuídos igualmente em 20 aquários de fibra de vidro, equipados com filtro biológico. Cinco dietas isoprotéicas com 32% de proteína bruta na primeira fase (40 dias) e com 28% de proteína bruta na segunda fase (74 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
3
0
6
Order By: Relevance
“…However, these data are in contrast with those obtained by (Mutlu et al, 2015) indicated that the differences of growth rates between control and copper sulfate-exposed groups were not significant (P>0.05) at the end of 35, 65 and 95 days. Moreover, vitamin C or β-glucan supplementation markedly improved growth performance and feed efficiency parameters which agree with (Baccarin and Pezzato, 2001). When fed lower content of protein (28.0% DP/3000 kcal DE/kg), but with addition of vitamin C (400 and 600 mg kg-1) and ß-glucan (0.10.8%), that species presented a satisfactory performance even with shorter periods of time (six weeks) than the ones observed in the present study (Falcon, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…However, these data are in contrast with those obtained by (Mutlu et al, 2015) indicated that the differences of growth rates between control and copper sulfate-exposed groups were not significant (P>0.05) at the end of 35, 65 and 95 days. Moreover, vitamin C or β-glucan supplementation markedly improved growth performance and feed efficiency parameters which agree with (Baccarin and Pezzato, 2001). When fed lower content of protein (28.0% DP/3000 kcal DE/kg), but with addition of vitamin C (400 and 600 mg kg-1) and ß-glucan (0.10.8%), that species presented a satisfactory performance even with shorter periods of time (six weeks) than the ones observed in the present study (Falcon, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Baccarin & Pezzato (2001) and observed changes in the body constitution of fish supplemented with S. cerevisiae, which might cause a zoothecnical drawback due to the reduction of the proteic concentration and the storage of lipids. Those researchers reported that the biological value of protein that come from yeast presents imbalance of amino acids, resulting in the reduction of protein synthesis, turning it into energetic reserves.…”
Section: Resultsmentioning
confidence: 98%
“…The groups were completely randomized with a 2 × 2 × 3 factorial design: with and without supplementation, 2 stimulations (oily solution without S. agalactiae vaccine and vaccination) and 3 evaluation times (6, 24 and 48 h; n = 7 at each evaluation time). The feed (NRC 1993) contained isoprotein (32.0% DP), isoenergy (3200 kcal kg −1 of DE) and isophosphorus (3.0% P available phosphorus) with the same level of gross fiber (5.0%) (Baccarin & Pezzato 2001) The ingredients were finely ground (0.7 mm), homogenized, pelleted in a pellet mill (model 20A,California Pellet Mill) at 40°C and dried in a heated chamber with forced air circulation (55.0°C, 24 h). The pellets were fractionated into compatible diameters (6 mm) and stored at a temperature of −20.0°C.…”
Section: Storage Experimental Design and Feedmentioning
confidence: 99%